Designing Creative Industry Center in Medan City with Tropical Architecture Approach - Yohannes Sepril Duarsa Siagian; Hajar Suwantoro (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Medan as the capital city of North Sumatra has rapid economic development, for instance in the creative industry sector. This development is in line with the large productive age rate which reached 69.99% and the increase in intellectual property applications to the Ministry of Law and Human Rights from North Sumatra. The rapid growth of the creative industry and the large number of productive ages require the right platform to encourage further development of the creative industry in the city of Medan. The right place for this is the creative industry center building facility. The facility can be used as a center for creative industry executants to develop their businesses in various ways, such as workshops, exhibitions, seminars, and so on. This facility was designed with a tropical architectural approach in an effort to respond well to the building's environment.